2009
DOI: 10.1111/j.1502-3885.2009.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the reliability of the JEOL FEGSEM 6500F electron microprobe for quantitative major element analysis of glass shards from rhyolitic tephra

Abstract: Davies, S. M. 2010 (January): Testing the reliability of the JEOL FEGSEM 6500F electron microprobe for quantitative major element analysis of glass shards from rhyolitic tephra.Electronprobe microanalysis is now widely adopted in tephra studies as a technique for determining the major element geochemistry of individual glass shards. Accurate geochemical characterization is crucial for enabling robust tephra-based correlations; such information may also be used to link the tephra to a specific source and often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…15B) at identical microprobe conditions, thus contra-indicating analytical problems as source of the trends observed in the Deception Island data. Moreover, studies on inter-microprobe differences of rhyolitic glass analyses found good comparability applying different sets of analytical parameters (Coulter et al, 2010), including also a set of parameters similar to ours (see section 5: methodology).…”
Section: Microprobe Glass Datasupporting
confidence: 65%
“…15B) at identical microprobe conditions, thus contra-indicating analytical problems as source of the trends observed in the Deception Island data. Moreover, studies on inter-microprobe differences of rhyolitic glass analyses found good comparability applying different sets of analytical parameters (Coulter et al, 2010), including also a set of parameters similar to ours (see section 5: methodology).…”
Section: Microprobe Glass Datasupporting
confidence: 65%
“…However, in other cases, geochemical differences can be subtle, as noted previously, and hence high levels of precision and accuracy are required for successful correlation and identification. Further, small differences between results may be produced by different laboratories (as can occur with all analytical systems) but these have been, and continue to be, addressed by use of appropriate standards and agreed protocols (Froggatt, 1992;Turney et al, 2004) and by interlaboratory comparison exercises (Hunt and Hill, 1996;Potts et al, 2002;Coulter et al, 2010). re-analysed samples of potential and likely correlatives from reference collections at the same time they analysed the unknown tephras to help eliminate possible small, day-to-day differences in probe calibration.…”
Section: Electron Probe Microanalysis Of Glassmentioning
confidence: 99%
“…The X-rays produced are of particular energies and wavelengths relating directly to individual elements, and their intensities are a measure of specific element abundance (Shane, 2000;Reed, 2005;Coulter et al, 2010). Typically, around 10 to 13 elements -Si, Al, Ti, Fe, Mn, Mg, Ca, Na, K, and P, and also S, F, and Cl -are able to be assayed (depending in part on glass composition) (Hayward, submitted for publication).…”
Section: Electron Probe Microanalysis Of Glassmentioning
confidence: 99%
See 2 more Smart Citations